Analisis transparansi pengelolaan keuangan desa berdasarkan Permendagri No. 20 Tahun 2018 (Studi kasus pada Pemerintah Desa Tosoa Kecamatan Ibu Selatan Kabupaten Halmahera Barat) - Tede, Reni; Budiarso, Novi Swandari; Kapojos, Peter M. (Yayasan Widyantara Nawasena Raharja, 2024)
This research was conducted to determine the transparency of management village finance in Tosoa village starting from the planning stage, implementation and accountability. The purpose of this study was to find out how transparent village financial management is in Tosoa village, Ibu Selatan District, West Halmahera Regency, based on Permendagri Number 20 of 2018. The analytical method used in this thesis research is a qualitative research that is descriptive and is made based on the result of interviews with several research informants. As for the informants in this study were village officials, in this case the village head, the village secretary, as well as the village finance offier. The results of this study indicate that transparency in village financial management in Tosoa village starting from te planning, implementation and accpuntability stages has been carried out openlyan in accordance with Permendagri Number 20 of 2018.